Cross-coupling of hydrogeochemical evolution and groundwater flow systems distribution pattern in an arid inland plain in northwestern China - Hu Su; Yinger Deng; Liqiang Ma; Pengjie Li; Hongkun Yang; Lin Chen (Journal of Hydrology: Regional Studies, 2025)
Study region: The Aksu River Basin in the northwest margin of Tarim Basin, China. Study focus: This investigation employs hydrochemical signatures coupled with isotopic tracers to characterize groundwater flow systems (GFSs) distribution patterns in the hyperarid Aksu Basin. The research delineates climate-driven recharge cyclicity and the mutual feeding relationship with the surface river-lake and aquifer systems, while establishing a the hydrogeological conceptual model of GFS that advances the theory of GFSs in arid Marine inland basins. New hydrological insights for the region: Hydraulic heads, hydrochemical parameters and isotopic signatures along basin-scale transects and vertical profiles are the effective indicators for identifying differently hierarchical GFSs. Due to the fractionation effect of stable isotopes in surface water and groundwater, the δ18O and δ34S values of different sections show different degrees of depletion and enrichment features horizontally and vertically, reflecting the occurrence of interactions between them. Combined with the development characteristics of Laolongkou swamping, soil salification near Kezile Town, artefact area in the forward alluvium of Gumubiezi Mountain and localized stagnant-flow fluoride-arsenic anomaly enrichment zones, it is fundamentally revealed that they belong to different local GFSs. Furthermore, the vertical zonation of 3H and 14C isotope concentrations and unconformable distribution of groundwater residence time further illustrate the hydrodynamic cycle of regional GFSs in the mid-deep aquifer system. The hydrodynamic characteristics and hydrochemical distributions corroborated the existence of a multi-hierarchy nested GFS pattern in the Aksu River Basin.